Corrosion-resistant metallic coatings for aluminum alloys by cold spray. (December 2022) - Witharamage, Chathuranga S.; Alrizqi, Mohammed A.; Chirstudasjustus, Jijo; Darwish, Ahmed A.; Ansell, Troy; Nieto, Andy; Gupta, Rajeev K.
Abstract: An Al-V alloy powder produced by high-energy ball milling has been cold sprayed on an AA2024-T3 substrate. The corrosion resistance of cold sprayed alloy, represented by the corrosion current density and pitting potential, was significantly higher than the substrate. Furthermore, a zero-resistance ammeter test revealed that the coating was anodic to the substrate, which would provide cathodic protection in any event of coating breakdown. The wear resistance of the coating was almost four times higher than that of the substrate. Graphical Abstract: ga1 Highlights: Successful cold spraying of ball-milled Al-V alloy powder on an AA2024-T3 substrate. Nanocrystalline Al-V alloy coating with high solid solubility of V in Al by cold spray. 43 times decreased corrosion current density by cold spraying Al-V alloy. Significantly increased pitting potential and wear resistance by cold spraying. Highly corrosion resistant and sacrificial coating.